Credit System for Senior High School Student: An Experiment to Meet with the Various Student Learning Pace - Budiyanto, Budiyanto; Rachim, Alfa Setya; Istyarini, Istyarini (Indonesian Journal of Curriculum and Educational Technology Studies, 2020)
The implementation of credit system is not something new in Indonesian education system, especially for higher education, but its implementation in senior high school is something new and challenging, because it focuses on the holistic learning service of each student. This research aims to describe the implementation of credit system in senior high school in Salatiga as a sample of the study and its problem faced by the management of the school. By conducting qualitative approach, it can be concluded that the implementation of credit system in public senior high school 1 Salatiga is working very well according to its compliance with the policy and manual from the Ministry of Education and Culture. But there are several obstacle come from the teachers and students who do not really comprehend yet the basic concept of the credit system policy, for instance most of the student want to graduate on the same time in which it is contradict with the orientation of the credit system to facilitate each student to learn and graduate according to their own learning pace. Abstrak Implementasi system kredit semester (SKS) di Indonesia bukan hal baru, terutama bagi perguruan tinggi, namun bagi sekolah—terutama sekolah menengah atas (SMA) adalah hal baru yang cukup menantang, karena memang fokus pada melayani secara holistik kebutuhan belajar tiap siswa. Penelitian ini bertujuan untuk menggambarkan implementasi dan problem yang dihadapi dalam penerapan kebijakan SKS tersebut di SMA Negeri 1 Salatiga sebagai salah satu contoh penerapan. Dengan menggunakan pendekatan kualitatif penelitian ini menyimpulkan bahwa secara umum pelaksanaan SKS di SMA N 1 Salatiga dapat berjalan dengan baik sesuai dengan kebijakan dan panduan dari Kementerian Pendidikan dan Kebudayaan. Namun pada dasarnya terdapat beberapa kendala yang berasal dari guru dan siswa yang belum sepenuhnya konsep dasar dari kebijakan SKS tersebut. Misal, banyak siswa seangkatan ingin lulus Bersama-sama yang mana hal ini berlawanan dengan orientasi dari kebijakan SKS untuk memfasilitasi tiap siswa untuk dapat belajar dan lulus sesuai dengan kecepatan belajar masing-masing.